(untitled) (World Economics and Finance Bulletin, 2026)
This article examines the issues of improving the efficiency of placement and management of small industrial zones using the Khorezm region as a case study. The research analyzes the key factors affecting the performance of small industrial zones, including territorial economic potential, local resources, market infrastructure, and the institutional environment, based on an integrated approach. An integrated model for assessing the efficiency of placement and operation of small industrial zones is developed, with weighting coefficients determined through expert evaluation methods. In addition, mechanisms for digitalizing the selection of investment projects and the allocation of production areas and land plots are proposed. The research findings contribute to increasing the transparency of managerial decisionmaking, reducing the impact of the human factor, and accelerating regional socio-economic development.